A System Theory Approach in Management of Community Health Centers (Mid-Level Health Organizations) in India - Paras Mal Soni; Shilpi Khandelwal (Asian Pacific Journal of Health Sciences, 2021)
Health-care delivery in India has been developed at three levels specifically, primary, secondary, and tertiary. The secondary level of health-care basically includes Community Health Centers (CHCs), constituting the First Referral Units. The health-care system is that the organization (e.g. hospital, clinic, and nursing home) that has infrastructure and completely different complementary resources to support the work and development of care teams and microsystems. The application of system theory at mid-level will enhance the further managerial promptness at this level. In this paper, we described system theory as the process of identifying the systems of health-care delivery at the CHC level and subsystems with in CHCs and its interactions with environment and other systems.
Keywords: Community health center; Health-care delivery; Open system; India